Time traveler confirms five minute hypothesis! - Sorensen, Roy (Synthese, 2024)
Conclusion: What matters for any norm is personal time rather than time. Personal time is a time-like relation (roughly, the time measured by your wristwatch) that knits together scattered temporal parts so that they conform to familiar patterns. David Lewis introduced personal time as an interpretive fiction that allows readers to consistently read fictions about time travelers. Inadvertently, Lewis thereby introduced a metric for all value (including prudence, morality, and aesthetics). Premise: The application of any norm requires personal time rather than time. This principle of reasoning is illustrated by recent debate about Bertrand Russell’s 5 minute hypothesis. This skeptical hypothesis would be undercut if one needs more than 5 minutes to reason about it. But what reasoners actually require is personal time. Once its priority over time is established for the norms governing reasoning, all remaining norms synchronize to personal time. Re-writing diachronic epistemology in Lewis’ atemporal vocabulary salvages much of what is literally true – and exposes the primacy of causation.